THE FISHBOWL STRATEGY: AN EFFECTIVE WAY TO IMPROVE STUDENTS’ SPEAKING ABILITY - Dominicus Yabarmase (Universitas Katolik Indonesia Atma Jaya, 2013)
Speaking is one of essential language skills in communication.Language teachers are expected to bring an effective method inclassroom to improve students’ speaking skills. Based on thepreliminary study in language classroom SMA Xaverius Ambon,teachers had limited knowledge of creative method in teachingspeaking which can be integrated to curriculum. Thus, the use ofFishbowl strategy can provide opportunity in the form of Fish andthe Bowl for each student to practice speaking in the classroomwhile considering about current curriculum. In the Fishbowl, eachstudent can take a turn to deliver the ideas, and everyone has theequal chance to speak. This research focused on theimplementation of Fishbowl strategy to improve speaking abilityof 30 students from first grade of SMA Xaverius Ambon. Theresearch methodology was a classroom action research. At the endof implementing fishbowl, the researcher gave the questionnaire toknow students’ perception toward the use of Fishbowl strategy.Based on the research findings, there were 26,6% successfulstudents at the pre-test. After conducting fishbowl, 100% ofstudents in the classroom had improvement in their speaking skillbecause each of them had more chance to speak up somethingrelated to the topic givenKeywords: Speaking, Fishbowl strategy, action research